Literature Review: Cost Calculation of Blood Services in Some Countries (Based on HDI Level) - Andani, Khisula Riski; Ernawaty, Ernawaty (Unnes Journal of Public Health, 2022)
The blood processing replacement costs (BPPD) establishment in Indonesia is an incomprehensive cost calculation for blood services. Several countries have calculated costs for blood services at health care institutions through an activity framework plus generated blood products and components costs as well as blood services fees. This study aims to discuss the cost calculation method for blood services carried out in Zimbabwe, Canada, United Kingdom, Greece and India. It was a literature review conducted by accessing scientific articles sourced from the Google Scholar database. A total of 11 articles were collected, but only 5 with relevant topics were discussed. Blood service cost calculation provides information of various activities involved in producing a product and service. Also, blood service framework model determination was needed as a cost center for estimation to prevent duplication. Each activity's total output from the cost center was used in calculating the unit cost of the activity or product. The blood products and components include whole blood, red blood cells, platelets, plasma (FFP), and cryoprecipitate. Each of the blood components require a different cost determined by the activity involved in their production.